2020
DOI: 10.7759/cureus.8871
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Vaccine Component for COVID-19: A Comprehensive Review of Global Vaccine Development Efforts

Abstract: The whole world is concerned about the pandemic of coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), due to fatality of this condition. This has become a public health emergency of international concern. No specific vaccine and medicine have proven effective in large-sized trials at this time. With the rapidly increasing number of positive cases and deaths, there is a dire need for effective treatments and an effective vaccine for prevention. An urgent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…SARS-CoV-2 may directly cause acute pancreatitis due to the higher expression of ACE2 receptors in pancreatic islets. Acute pancreatitis can be secondary to intense inflammatory response and cytokine storm induced by COVID-19 infection [16,17]. In our case, the patient had laboratory evidence of marked systemic inflammation with increased ESR, CRP, and D-dimer.…”
Section: Discussionmentioning
confidence: 65%
“…SARS-CoV-2 may directly cause acute pancreatitis due to the higher expression of ACE2 receptors in pancreatic islets. Acute pancreatitis can be secondary to intense inflammatory response and cytokine storm induced by COVID-19 infection [16,17]. In our case, the patient had laboratory evidence of marked systemic inflammation with increased ESR, CRP, and D-dimer.…”
Section: Discussionmentioning
confidence: 65%
“…The bacille Calmette-Guerin vaccine is another live-attenuated vaccine consisting of the bacteria that causes bovine tuberculosis ( Mycobacterium bovis ). Remarkably, bacille Calmette-Guerin (BCG) vaccination seems to demonstrate non-specific protective effects against other respiratory tract infections ( 17 ). The analysis has shown that countries with high coverage of BCG have a low death rate from COVID-19 ( 94 ).…”
Section: Covid-19: Therapeutic Approachesmentioning
confidence: 99%
“…1a ). Several other nonstructural proteins are also encoded by the viral genome (RNA polymerase, RdRp; papain-like protease, PLpro; coronavirus main protease, 3CLpro) ( 17 ). A representative transmission electron microscope (TEM) image of SARS-CoV-2 viruses in host cells is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the innovation and development of technologies in mRNA sequences engineering, mRNA production, and mRNA vaccine delivery materials make the COVID-19 mRNA vaccines possible [152] . By April 2021, more than 14 mRNA vaccines are being developed against COVID-19 by researchers across the world [ 148 , 153 , 154 ]. The Phase III clinical trials of mRNA vaccines BNT162 (Pfizer/BioNTech Inc.) and mRNA-1273 (Moderna Inc.) [155] , [156] , [157] , [158] , [159] , [160] have been finished ( Table 1 ); the vaccine products have been approved for commercial use.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%